DEGREE OF SUSPICION OF PERIPHERAL ARTERY DISEASE AMONG GERIATRICS AND POLICEMEN IN ILIGAN CITY, PHILIPPINES - Jan Igor Temple Galinato (Belitung Nursing Journal, 2019)
Background: Peripheral artery disease is a type of cardiovascular disease which belongs to vascular system disease and ranked the second most common non transmissible disease that cause death in the Philippines. The ankle brachial index (ABI) constitutes simple, non-invasive, cost-effective method for the early detection of peripheral artery disease (PAD) which complements assessment of cardiovascular risk. Objective: The study aims to determine who are at risk of peripheral artery disease among the Geriatrics and Policemen in Iligan City. Methods: It utilized descriptive-correlational-comparative research design and purposive sampling method. The data were gathered among 40 respondents: 20 Geriatrics and 20 policemen from Camp Tomas Cabili in Iligan City with the use of modified standardize questionnaire from Southern California Health Specialist Peripheral Artery Disease Patient Questionnaire. Results: Results showed majority (50%) of respondents were 50 years old and above; most (65%) were male. Pearson Correlational Coefficient shows that, among the demographic profile of the respondents, only age and lifestyle (diet and exercise) had a significant relationship with their degree of suspicion of having PAD. On the other hand, there was no significant relationship between gender, history of heredo-familial diseases, smoking, alcohol drinking habits, and the respondent’s degree of suspicion of having PAD. The result contradicts the nursing maxim that smoking is the most important risk factor for PAD; as in this case, even if most of the respondents were non-smokers and non-alcoholics, their poor diet and exercise alone increased their risk or degree of suspicion of having PAD. Conclusion: While age is beyond the control of the respondents, there is much that they could do to improve their lifestyle (diet and exercise) to lessen their risks for PAD. An institutional cafeteria serving nutritious food and exercise gyms could greatly benefit both the geriatrics and the policemen.